Analysis of governmental open letters mobilizing residents in China during the COVID-19 pandemic - Liu, Qing (Discourse & society, 2023)
In response to the threat of COVID-19, China initiated a nationwide campaign. Ideological work such as explaining the implemented policies and persuading the public always took a central role in mobilization, and it has been emphasized by Chinese government during Covid-19 as well. The legitimation discourse used in the campaign is the focus of the current study. The investigation takes into consideration the political logic of the relationship between the central and local governments as well as their working mechanism. More specifically, a total of 84 open letters written by the local governments to mobilize residents during the COVID-19 pandemic were analyzed. The study integrated the CDA perspective, legitimation theory, and campaign-style governance and examined what ideological discourses are constructed in the open letters, what type of authority is constructed for legitimation, and what is the main communication style used. In addition, the study paid attention to the patterns among the different local government ranks. The findings revealed that moral appeal and political authority were the key elements of legitimation discourse, but governments with lower ranks exhibited a trend of de-ideologization. Meanwhile, impersonal politeness and direct bold command contradictorily co-existed in open letters of basic level local governments. These finding reveal that despite the top government’s centralized power, realization of ideological work in a national campaign is confined by the divergent and complicated realities of local governments.